TREN DAN PERKEMBANGAN PENELITIAN TOXIC WORKPLACE ENVIRONMENT TAHUN 1999-2023: ANALISIS BIBLIOMETRIK - Alisa, Juniar; Ardiani, Gusti Tia (Program Studi Manajemen Fakultas Ekonomi Universitas Siliwangi, 2025)
This study examines the development of research on toxic workplace environments using a bibliometric approach from 1999 to 2023. The research aims to answer questions related to publication trends, productive authors, active countries, and key topics in this field. Data collection involved extracting 125 articles from the Scopus database, which were then refined to 79 relevant publications through data cleaning in OpenRefine. Using VOSviewer and additional software like MS Excel, the study analyzed co-authorship networks, keyword occurrences, and citation trends. Findings reveal an increasing interest in toxic workplace environments over time, with a notable rise in publications and citations since 2006. Sexual harassment and hostile work environments emerged as prominent keywords, indicating a focus on negative interpersonal interactions. This research contributes to understanding the dynamics of toxic work environments and highlights the need for organizations to address these issues, benefiting employee well-being and productivity.